2009
DOI: 10.1128/jvi.02293-07
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of the Influenza A Virus Nucleocapsid Protein with the Viral RNA Polymerase Potentiates Unprimed Viral RNA Replication

Abstract: The influenza A virus polymerase transcribes and replicates the eight virion RNA (vRNA) segments. Transcription is initiated with capped RNA primers excised from cellular pre-mRNAs by the intrinsic endonuclease of the viral polymerase. Viral RNA replication occurs in two steps: first a full-length copy of vRNA is made, termed cRNA, and then this cRNA is copied to produce vRNA. The synthesis of cRNAs and vRNAs is initiated without a primer, in contrast to the initiation of viral mRNA synthesis, and requires the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
89
0
4

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(95 citation statements)
references
References 46 publications
2
89
0
4
Order By: Relevance
“…3,9 This observation, together with the phenotype of virus mutants that are temperature-sensitive for vRNA synthesis but show normal accumulation of cRNA at restrictive temperature, [100][101][102] suggest that most of the cRNA synthesis that takes place in the infection uses the parental RNPs as templates. The large differences in cRNA and 115,116 and in vivo, 88,102 although replication of short RNA templates can proceed in the absence of NP. 61,117 The incorporation of NP into new vRNPs is facilitated by the activity of cellular factors UAP56 and Tat-SF1, that may act as chaperones.…”
Section: Virus Genome Amplificationmentioning
confidence: 99%
“…3,9 This observation, together with the phenotype of virus mutants that are temperature-sensitive for vRNA synthesis but show normal accumulation of cRNA at restrictive temperature, [100][101][102] suggest that most of the cRNA synthesis that takes place in the infection uses the parental RNPs as templates. The large differences in cRNA and 115,116 and in vivo, 88,102 although replication of short RNA templates can proceed in the absence of NP. 61,117 The incorporation of NP into new vRNPs is facilitated by the activity of cellular factors UAP56 and Tat-SF1, that may act as chaperones.…”
Section: Virus Genome Amplificationmentioning
confidence: 99%
“…In contrast to RAF-2p48/UAP56, Prp18 enhances viral RNA synthesis from vRNP, suggesting that Prp18 functions as a chaperone of NP on the virus genome. The binding of NP to the virus genome is required to form the vRNP template for an efficient elongation reaction by RdR Pol (8)(9)(10)(11)(12). A recent structural model of RdR Pol of a segmented negative-strand RNA virus led to the proposal that the disruption of the vRNP structure during template reading is restricted around the active center due to the proximity of the entry and exit channels of template (42).…”
Section: Discussionmentioning
confidence: 99%
“…It has been postulated that NP encapsidates de novo RNA and regulates the RdR Pol function through the interaction with PB1 and PB2 (8)(9)(10)(11)(12). It has been reported that encapsidation is coupled with replication processes (11) and initiated by successive targeting of the exogenous NP monomer to RdR Pol, which is distinct from the replicative polymerase and binds to the 5= end of nascent RNA (13), and additional NPs are then subsequently recruited by NP-NP oligomerization (14).…”
Section: Importancementioning
confidence: 99%
“…Based on the RNA-binding capacity of NP, some have proposed that the protein promotes cRNA/vRNA synthesis by altering the panhandle structure (7)(8)(9). In addition, biochemical studies have suggested that NP can associate directly with the polymerase, possibly preventing its cap snatching activity and promoting unprimed transcription (10)(11)(12). Other models suggest that the polymerase itself dictates the switch, perhaps through the actions of individual subunits, including polymerase acidic protein (PA) and polymerase basic 2 protein (PB2) (13,14), or by operating in cis to transcribe mRNA and in trans to produce cRNA (15).…”
mentioning
confidence: 99%